Secretory IgA Antibodies from Plants - Wycoff, K. (Current pharmaceutical design, 2005)
Secretory IgA (SIgA) is the antibody type produced in both mammals and birds that protects the body from infection at mucosal surfaces. While monoclonal IgG antibodies, particularly those against tumor antigens, have received a great deal of attention, both scientific and commercial, as immunotherapeutic agents, the potential of SIgA antibodies has only recently begun to be exploited. Part of the reason for this is that SIgA production in vivo normally requires the cooperation of two different cell types, and single animal cell systems for monoclonal SIgA production are inefficient. Transgenic plants are currently the most productive and economical system for making SIgA. The only monoclonal SIgA to be tested therapeutically in a human clinical trial is a product called CaroRx, made in transgenic tobacco, which is designed to block adherence to teeth of the bacteria that causes cavities. This antibody accumulates to high levels in the leaves of tobacco, where it is located primarily in the endoplasmic reticulum. The antibody can be efficiently purified using the affinity reagent protein G. Topical oral treatment in human subjects was safe and effective. Characterization of the expression, secretion, purification and therapeutic use of this antibody serves as a model for additional plant-made therapeutic SIgA antibodies under development.